Overexpressed EDIL3 predicts poor prognosis and promotes anchorage-independent tumor growth in human pancreatic cancer - Jiang, Shu-Heng (Oncotarget, 2015)
Epidermal Growth Factor-like repeats and Discoidin I-Like Domains 3 (EDIL3), an extracellular matrix (ECM) protein associated with vascular morphogenesis and remodeling, is commonly upregulated in multiple types of human cancers and correlates with tumor progression. However, its expression pattern and underlying cellular functions in pancreatic ductal adenocarcinoma (PDAC) remain largely unexplored. In current study, we observed that expression of EDIL3 was significantly up-regulated in PDAC compared with normal controls in both cell lines and clinical specimens. In addition, elevated EDIL3 expression was positively correlated with patients’ TNM stage and T classification. Kaplan-Meier analysis indicated that high EDIL3 expression was significantly associated with shorter overall survival times in PDAC patients. Multivariate Cox regression analysis confirmed EDIL3 expression, age, lymph node metastasis and histological differentiation as independent prognostic factors in PDAC. Knockdown of EDIL3 showed no significant influence on cell viability, migration, invasion and starvation-induced apoptosis, but compromised anoikis resistance and anchorage independent tumor growth of PDAC cells. Meanwhile, treatment with recombinant EDIL3 protein markedly promoted anoikis resistance and anchorage independent tumor growth. Mechanistically, we demonstrated that altered protein expression of Bcl-2 family might contribute to the oncogenic activities of EDIL3. In conclusion, this study provides evidences that EDIL3 is a potential predictor and plays an important role in anchorage independent tumor growth of PDAC and EDIL3-related pathways might represent a novel therapeutic strategy for treatment of pancreatic cancer.